2021
DOI: 10.1002/path.5677
|View full text |Cite
|
Sign up to set email alerts
|

What do we need to know and understand about p53 to improve its clinical value?

Abstract: Few proteins are more studied than the p53 tumour suppressor, but what have we learned from these studies and what do we really know about p53 that can benefit clinical practice? The DNA sequence encoding p53 is frequently mutated in cancers but the functional outcomes of single mutations, in respect to loss or gain of different activities, especially in relation to immune evasion, are not clear. This illustrates p53's complexity which even after 40 years keeps providing surprises, but also explains why it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 96 publications
1
12
0
Order By: Relevance
“…The p53 gene has evolved from an ancestral p53/p63/p73 gene, which gave rise to three p53-related genes, with distinct roles in mammals ( Belyi et al 2010 ; Rutkowski et al 2010 ; Karakostis et al 2016 ; Siau et al 2016 ; Hendler et al 2021 ). The tp53 transcription factor is a tumor suppressor with key roles in oncogenesis ( Mantovani et al 2019 ; Salomao et al 2021 ). It involves two N-terminal transactivation domains (TAD I and TAD II), a DNA-binding domain (DBD), and a C-terminal oligomerization domain ( Wallace et al 2006 ; Logotheti et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p53 gene has evolved from an ancestral p53/p63/p73 gene, which gave rise to three p53-related genes, with distinct roles in mammals ( Belyi et al 2010 ; Rutkowski et al 2010 ; Karakostis et al 2016 ; Siau et al 2016 ; Hendler et al 2021 ). The tp53 transcription factor is a tumor suppressor with key roles in oncogenesis ( Mantovani et al 2019 ; Salomao et al 2021 ). It involves two N-terminal transactivation domains (TAD I and TAD II), a DNA-binding domain (DBD), and a C-terminal oligomerization domain ( Wallace et al 2006 ; Logotheti et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, numerous cellular and animal model studies indicate that an unbalance in p53 isoform expression causes cancer, premature aging, and degenerative diseases ( Fujita 2019 ). An abnormal expression of p53 isoforms, or mis-regulation of posttranslational modifications (PTMs) mediating the interactions of p53 pathway, may be induced by mutations leading to carcinogenesis ( Khoury and Bourdon 2011 ; Karakostis et al 2019 ; Salomao et al 2021 ). Importantly, experiments on mice have shown that extra copies of the p53 gene can be introduced to generate “super p53” animals carrying three or four functional copies of p53, accurately reproducing the behavior of the endogenous gene but with an enhanced response to DNA damage ( Garcia-Cao et al 2002 ; Moding et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For tumors with mutant p53, therapeutic agents are developed to reactivate mutant p53 or promote its degradation ( Chen et al, 2021 ). Targeting the p53 signaling pathway has been extensively reviewed by a number of investigators ( Hernández Borrero and El-Deiry, 2021 ; Huang, 2021 ; Liu et al, 2021 ; Salomao et al, 2021 ). At least theoretically, therapeutic restoration of inactivated tumor suppressors is more challenging than inhibiting an oncogenic target.…”
Section: P53 In Cancermentioning
confidence: 99%
“…As expected, the dynamic presence of these genes on the mutational cancer map, has made the p53 pathway-and especially the TP53 component-an attractive therapeutic target. Among a plethora of p53-targeting strategies, the most promising fall into one of the following categories: (i) restoring the function of p53 protein or (ii) impeding the interaction between p53 and its main negative regulator, the MDM2 E3 ubiquitin ligase [35,59,60]. In this context, eprenetapopt (APR-246), a mutant-p53 conformation resetting agent, is probably the most promising compound [61] and the only therapy of this category that is currently being tested in a phase III clinical trial (NCT03745716); on the other hand, a phase III trial of idasanutlin (NCT02545283), another emerging MDM2 inhibitor, was recently terminated due to low efficacy.…”
Section: The P53 Pathwaymentioning
confidence: 99%